COOPERATIVE ASSESSMENT WRITING PRACTICES AT AN ACEHNESE PRIVATE UNIVERSITY: HELPING OR TROUBLING? - Akmal, Saiful; Dahliana, Syarifah; Fadhila, Rani (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2019)
A good writing skill could be a benchmark of someone’s good ability in English. This study aims find the way how the practice of cooperative assessment can diminish errors and mistakes in students’ writing and to see students’ view towards cooperative assessment method in writing class. Qualitative approach by using case study method was selected, and the data were taken by means of observation, document analysis and interview towards the fourth semester students of Serambi Mekah University Banda Aceh, Indonesia in 2018/2019 academic year. The findings shown that there were three techniques of cooperative assessment that may lessen errors and mistakes in students’ writing, namely; peer review, lecturers’ feedback and classroom reviewing activity. In students’ view, cooperative assessment has some benefits (improving grammatical awareness, improving students’ vocabularies, and improving the structure of students’ writing) as well as drawbacks (peer errors in editing, and time consuming). Therefore, it is recommended that students make their errors and mistakes diary notes and lecturers are advised to start making grammar errors and mistakes checklists based on the learning objectives for students’ peer reviewing practice.